Technical progress and the share of labor income - Xun Zhang; Chen Wang; Guanghua Wan; Zhi Luo (Asian Development Bank Institute (ADBI), 2017)
Changes in the labor share of national income affect inequality (Piketty 2014). This paper aims at investigating the relationship between the labor share and technical progress, based on provincial data of the People's Republic of China (PRC) from 1978 to 2012. Our main empirical results show that technical progress in the PRC had been mostly capital biased, contributing to the fast rises in income inequality in the PRC. However, the employment proportion of state-owned enterprises seems to have played a role in offsetting this negative effect, helping contain inequality. In recent years, both effects have become more significant and larger in absolute terms.
Keywords: D33; E25; L32; O33; 330; Economics; Industry and trade; China; People's Republic of